The Effect Of Financial Leverage, Capital Structure, Intellectual Capital On Financial Performance Company Size As A Moderating Variable - Wahyuni, Wahyuni; Hermuningsih, Sri; Sari, Pristin Prima (E-Jurnal Akuntansi, 2024)
The increasing development of the business world requires maximum performance from the company’s resources, both tangible and intangible assets, not only focusing on marketing or sales but also focusing on the financial sector. This research aims to determine the effect of financial leverage, capital structure and intellectual capital on financial performance with company size as a moderator in mining sector companies listed on the Indonesia Stock Exchange, with a sample of  92 data, using the purposive sampling method and moderated regression analysis (MRA). The results of the analysis show that the variables financial leverage and company size have a positive effect on financial performance. Meanwhile, the capital structure and intellectual capital variables negative  effect on financial performance. Company size weakens the influence of financial leverage on financial performance. Company size streangthens capital structure on financial performance.  Keywords: Financial Performance: Financial Leverage: Capital Structure: Intellectual Capital: Company Size.